2016
DOI: 10.1038/ncomms10913
|View full text |Cite
|
Sign up to set email alerts
|

Genetic suppression reveals DNA repair-independent antagonism between BRCA1 and COBRA1 in mammary gland development

Abstract: The breast cancer susceptibility gene BRCA1 is well known for its function in double-strand break (DSB) DNA repair. While BRCA1 is also implicated in transcriptional regulation, the physiological significance remains unclear. COBRA1 (also known as NELF-B) is a BRCA1-binding protein that regulates RNA polymerase II (RNAPII) pausing and transcription elongation. Here we interrogate functional interaction between BRCA1 and COBRA1 during mouse mammary gland development. Tissue-specific deletion of Cobra1 reduces m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 52 publications
5
39
1
Order By: Relevance
“…2c). A number of BRCA1-associated processes, including progesterone metabolism (Katiyar et al 2006;Ma et al 2006;Calvo and Beato 2011;Davaadelger et al 2019), RNA polymerase II transcription (Scully et al 1997;Krum et al 2003;Nair et al 2016), and unfolded protein response (UPR) (Yeung et al 2008), were enriched in both BCs and SCs. BRCA1 has been shown to inhibit progesterone signaling (Ma et al 2006) and reduction in BRCA1 level has been shown to increase expression of GRP78, a key UPR regulating gene (Yeung et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…2c). A number of BRCA1-associated processes, including progesterone metabolism (Katiyar et al 2006;Ma et al 2006;Calvo and Beato 2011;Davaadelger et al 2019), RNA polymerase II transcription (Scully et al 1997;Krum et al 2003;Nair et al 2016), and unfolded protein response (UPR) (Yeung et al 2008), were enriched in both BCs and SCs. BRCA1 has been shown to inhibit progesterone signaling (Ma et al 2006) and reduction in BRCA1 level has been shown to increase expression of GRP78, a key UPR regulating gene (Yeung et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Using mammary epithelial-specific knockout (KO) mouse models for Brca1 and Cobra1 , we recently demonstrated genetic complementation between these two genes during normal mammary gland development and tumor suppression 36 , 37 . Tissue-specific deletion of Cobra1 blocked ductal morphogenesis and alveologenesis, demonstrating a crucial role of COBRA1/NELF-B in adult tissue development.…”
Section: Introductionmentioning
confidence: 99%
“…Tissue-specific deletion of Cobra1 blocked ductal morphogenesis and alveologenesis, demonstrating a crucial role of COBRA1/NELF-B in adult tissue development. Of note, these resulting developmental defects of Cobra1 ablation were largely rescued by the loss of full-length BRCA1 expression through deletion of Brca1 exon 11 37 . Reciprocally, Cobra1 deletion reduced mammary tumorigenesis associated with Brca1 inactivation 37 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, deletion of Nelf-b in mESCs causes proliferation defects together with a blunted response to differentiation signals (Williams et al, 2015). Although these studies suggest crucial roles of NELF-mediated pausing in mouse embryonic development, the interpretation of these results could be complicated by other functions of NELF-B, such as the physical and functional interaction of NELF-B with the DNA repair protein BRCA1 (Aiyar et al, 2007; Nair et al, 2016; Ye et al, 2001). Thus, the direct role of Pol II pausing in mammalian embryonic development remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%